Generation and characterization of chimeric Tembusu viruses containing pre-membrane and envelope genes of Japanese encephalitis virus - Xu, Bangfeng; Liu, Xingpo; Yan, Dawei; Teng, Qiaoyang; Yuan, Chunxiu; Zhang, Zhifei; Liu, Qinfang; Li, Zejun (Frontiers in Microbiology, 2023)
Since its outbreak in 2010, Tembusu virus (TMUV) has spread widely throughout China and Southeast Asia, causing significant economic losses to the poultry industry. In 2018, an attenuated vaccine called FX2010-180P (180P) was licensed for use in China. The 180P vaccine has demonstrated its immunogenicity and safety in mice and ducks. The potential use of 180P as a backbone for flavivirus vaccine development was explored by replacing the pre-membrane (prM) and Envelope (E) genes of the 180P vaccine strain with those of Japanese encephalitis virus (JEV). Two chimeric viruses, 180P/JEV-prM-E and 180P/JEV-prM-ES156P with an additional E protein S156P mutation were successfully rescued and characterized. Growth kinetics studies showed that the two chimeric viruses replicated to similar titers as the parental 180P virus in cells. Animal studies also revealed that the virulence and neuroinvasiveness of the 180P/JEV-prM-E chimeric virus was decreased in mice inoculated intracerebrally (i.c.) and intranasally (i.n.), respectively, compared to the wild-type JEV strain. However, the chimeric 180P/JEV-prM-E virus was still more virulent than the parent 180P vaccine in mice. Additionally, the introduction of a single ES156P mutation in the chimeric virus 180P/JEV-prM-ES156P further attenuated the virus, which provided complete protection against challenge with a virulent JEV strain in the mouse model. These results indicated that the FX2010-180P could be used as a promising backbone for flavivirus vaccine development.